Antitumor Activity and Synthesis of 1, 2-Disubstituted Benzimidazoles in One-Pot Diverse Using Bismuth (III) Trifluoromethanesulfonate as Catalyst - Venkateswarlu, A; Harikrishna, M; Thriveni, P. (Asian Journal of Pharmaceutical Research and Development, 2024)
Various 1,2-disubstituted benzimidazoles were synthesized in a facile method using Bismuth(III) trifluoromethanesulfonate. It is suggested that formation of an intermediate between the substrate, amine and solvent gives the N-arylation process. This developed protocol is demonstrated by the efficient reactions involving various substituents ranging from electron-withdrawing groups to electron-donating groups.